Final environmental impact statement for the wilderness recommendation : Glacier Bay National Park and Preserve, Alaska. - United States. National Park Service. Alaska Regional Office. (Anchorage, Alaska : Alaska Regional Office, National Park Service, 1988)
"FES-88-41"--Stamped on cover. "NPS D-26A"--P. [3] of cover. Includes index. "September 1988."--P. [3] of cover. Cover title: Final environmental impact statement : wilderness recommendation : Glacier Bay National Park and Preserve/Alaska. Bibliography: p. 423-426. Mode of access: Internet.